Trisomy 19 and T(9;22) In a Patient with Acute Basophilic Leukemia - Alicia Rojas-Atencio; Karelis Urdaneta; Marisol Soto-Quintana; Francisco Alvarez Nava; Jenny Cañizales; Ernesto Solis (Case Reports in Pathology)
We report a case of acute basophilic leukemia with two coexisting clonal abnormalities, t(9;22) and trisomy 19. The blast showed positive reaction with myeloperoxidase but negative reaction with chloroacetate esterase and acid phosphatase. Metachromatic features of the blast were observed with toluidine blue stain. Ultrastructure study showed the presence of azurophilic granules in basophils and blast mast cells. Conventional and molecular cytogenetic studies revealed, t(9;22) with BCR/ABL positive and trisomy 19 in all metaphase cells. To our knowledge, this paper here is the first to present acute basophilic leukemia with trisomy 19 and t(9;22).